Differential quantities of carbon quantum dots incorporated feed on the growth and biochemical traits of Zebrafish (Danio rerio) - Malavika, V.; Anumol, R.; Rajan, M. R. (International Journal of Agricultural Technology, 2024)
Carbon quantum dots possess excellent hydrophilicity and cell permeability, making them very suitable for water-based and bio-related applications. However, there is a lack of research on the utilization of carbon quantum dots in fish feed. The results of this investigation showed that carbon quantum dots have high adsorption peaks at 355 nm in the UV-visible absorption spectra. SEM image was observed at the wavelength range from 13.77 to 13.69. EDAX spectrum showed three peaks and was located on the spectrum between 0.1 KeV and 3 KeV. FT-IR spectral observation was at a wavelength range from 4000 to 500 cm-1. The condition factor of Zebrafish exhibited an increase in all the experimental feeds as compared to the original condition. The consumption of feed, the efficiency of converting feed into growth, growth rate, percentage of growth, rate of growth relative to body size, assimilation of nutrients, metabolism, and efficiency of gross and net growth were all higher in F4 when it contained 1.5 ml of synthesized carbon quantum dots (1.39±0.28, 0.53±0.16, 0.05±0.005, 20.96±4.98, 1.36±0.28, 1.32±0.26, 5.85±2.14, and 6.08±1.30). The results conclude that 1.5 ml of carbon quantum dots incorporated in feed enhanced Zebrafish’s growth and biochemical traits